2007
DOI: 10.1111/j.1574-6968.2007.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineeredFusariumas a tool to evaluate the effects of environmental factors on initiation of trichothecene biosynthesis

Abstract: Fusarium graminearum was engineered for expression of enhanced green fluorescent protein gene (egfp) as a reporter regulated in a manner similar to Tri5, a key pathway gene in trichothecene biosynthesis. Using the transgenic fungus, it was found that the reporter gene was induced to express in aerial hyphae developed on trichothecene noninducing medium YG solidified by agar. Unexpectedly, the transcriptional activation of egfp was markedly suppressed by adding NaCl that does not significantly affect fungal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 26 publications
(32 reference statements)
3
46
1
Order By: Relevance
“…Importantly, our results are consistent with earlier works of Ochiai et al (2007), stating that non-lethal doses of triazole fungicides activate the Tri5 gene (trichothecene synthase) in Fusarium graminearum. Similar research performed on Fusarium verticillioides and Fusarium proliferatum strains has shown that sublethal doses of fungicides in combination with mild water stress and temperatures less than 35°C, significantly induced Fum1 expression with slight differences in both species (Marín et al 2013).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Importantly, our results are consistent with earlier works of Ochiai et al (2007), stating that non-lethal doses of triazole fungicides activate the Tri5 gene (trichothecene synthase) in Fusarium graminearum. Similar research performed on Fusarium verticillioides and Fusarium proliferatum strains has shown that sublethal doses of fungicides in combination with mild water stress and temperatures less than 35°C, significantly induced Fum1 expression with slight differences in both species (Marín et al 2013).…”
Section: Discussionsupporting
confidence: 82%
“…Miguel et al 2015) and secondary metabolite accumulation (e.g. Ochiai et al 2007;Mateo et al 2011;Marín et al 2013). The possible influence on the activity of the biosynthetic genes responsible for the production of mycotoxins can thus affect the efficiency of fungicidal treatments in controlling mycotoxin producers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very difficult to refer to this fact in view of the results collected so far. The observed differences between contents of fungal metabolites and phenolic acids between the population of K and OCH samples may be explained by the fact that sublethal concentrations of fungicides trigger trichothecene biosynthesis (Ochiai et al 2007;Müllenborn et al 2008). On the other hand, all fungicides (prothioconazole, tebuconazole, metconazole and prothioconazole + tebuconazole) used in the study reduced FHB index and deoxynivalenol (DON) levels according to Amarasinghe et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…In Aspergillus nidulans, endogenous and exogenous oxylipids differentially regulate sterigmatocystin and penicillin production (Tsitsigiannis & Keller, 2006). A number of recent reports have also implicated various compounds, such as H 2 O 2 , NaCl, azole fungicides, magnesium, carbon source and a large number of phytochemicals, in both positive and negative regulation of trichothecene production in vitro (Boutigny et al, 2008;Jiao et al, 2008;Ochiai et al, 2007;Pinson-Gadais et al, 2008;Ponts et al, 2006). However, in these studies the amount of DON produced in culture does not appear to approach the levels observed in infected heads, where concentrations can exceed 500 p.p.m.…”
Section: Introductionmentioning
confidence: 99%